Phytosociology and diametric structure of a fragment of Cerrado sensu stricto, Formoso do Araguaia, Tocantins, Brazil - Gama, Rafaella da Costa; Santana, Thiêssa Tamilla de Carvalho; Silva, Tayanne Graciette Nascimento; Andrade, Valdir Carlos Lima de; Souza, Priscila Bezerra de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The Brazilian Cerrado is composed of different phytophysiognomies, where one observes country, savanna and forest vegetation. Thus, a phytosociological survey was carried out to evaluate the diametric structure of a Cerrado fragment sensu stricto, Formoso do Araguaia - TO. Six rectangular plots of 500 m² each (10x50 m) were installed randomly, totaling 0.3 ha of sample area. In the plots we sampled all live and dead standing shrub trees with Circumference at Breast Height (CBH) ≥ 10 cm. There were 508 shrub-tree individuals sampled, being 480 live and 28 standing dead, distributed in 49 species and 27 families. The main families were Vochysiaceae, Fabaceae, Malpighiaceae, Sapotaceae and Melastomataceae. The Qualea parviflora Mart., Qualea grandiflora Mart., Pouteria ramiflora (Mart.) Radlk., Byrsonima coccolobifolia Kunth and Sclerolobium paniculatum Vogel presented the highest Values of Importance. The mean diameter of the individuals was 9.38 cm, the basal area was 4.71 m² ha-1 and density was 1,693.33 individuals ha-1. The diversity index of Shannon Wiener (H ') was 3.21 and the Pielou (J) equability was 0.83. Based on the results obtained it was observed that the fragment has high diversity with low ecological dominance and the inverted "J" diametric distribution pattern was observed in the community evidencing stable and auto regenerative populations.